Determination of trimethylamine N-oxide level and its metabolic precursors in biological material - Marchenko, A.B.; Ivasenko, S.A.; Turmukhambetova, A.A. (Вестник Карагандинского университета, 2016)
The level of trimethylamine N-oxide, exceeding the threshold indices, is a precursor to a number of diseases, leading to disability and death. In this context the definition of titers and the normalization of its levels in the body is one of the stages of preventive medicine. This review presents the methods for determining the levels of TMAO and its metabolic precursors in the biological material. The world practice mainly use the high performance liquid chromatography for TMAO quantitative determination in biological material, the detection is performed using tandem MS/MS spectroscopy, and in some cases nuclear magnetic resonance spectroscopy. The time-consuming sample preparation and complex combinations of the composition of the mobile phase are applied for effective separation and receiving of reliable results. Nevertheless, the problem of the quantitative and qualitative determination of TMAO and his predecessors not only hasn't lost the relevance, but has acquired the new horizons to improve this analysis in view of recent events in the scientific world.
Keywords: TMAO; choline and metabolites; atherosclerosis; trimethylaminuria; GC-MS/MS; NMRspectroscopy; HPLC-MS/MS; ion chromatography; analysis technique